Salidroside attenuates colistin-induced neurotoxicity in RSC96 Schwann cells through PI3K/Akt pathway. (1st June 2017) - Lu, Ziyin; Jiang, Guozheng; Chen, Ying; Wang, Jian; Muhammad, Ishfaq; Zhang, Ling; Wang, Rui; Liu, Fangping; Li, Rui; Qian, Feng; Li, Jichang
Abstract: Neurotoxicity is a key dose-limiting factor for colistin therapy. This study aimed to investigate the protective effect of Salidroside on colistin-induced neurotoxicity in RSC96 Schwann cells and the underlying mechanisms. After Salidroside (12.5, 25, 50 μg/mL) treatment for 2 h, the cells were cultured with 250 μg/mL colistin for 24 h. In order to investigate the role of phosphatidylinositol 3-kinase/protein kinase B (PI3K/Akt) pathway, the cells were pre-treated with LY294002 (12.5 μmol/L, a specific inhibitor of PI3K phosphorylation) for 1 h before Salidroside (50 μg/mL) treatment, then were co-cultured with colistin (250 μg/mL) for 24 h. The results showed that colistin treatment could induce apoptotic cell death which was associated with oxidative stress injury. Salidroside could reduce colistin-induced neurotoxicity, decrease the effect of colistin on the reduced expression levels of p-Akt and Bcl-2, and increased the expresion of Bax, release of Cyt c, and activation of caspase-3. However, the protective effect of Salidroside against colistin-induced apoptosis was partly abolished by LY294002. These findings suggest that Salidroside could attenuate colistin-induced neurotoxicity in RSC96 Schwann cells via the PI3K/Akt pathway. Highlights: Colistin can induce RSC96 cells injury by oxidative stress. Salidroside alleviated colistin-induced RSC96 cells injury. Salidroside possesses its protective effect partly via activated the PI3K/Akt signaling.